Cardioprotective Strategies for Doxorubicin-induced Cardiotoxicity: Present and Future - A. M. Chaulin; D. V. Duplyakov (Рациональная фармакотерапия в кардиологии)
The improvement of drugs and protocols of chemotherapeutic treatment has led to improved outcomes and survival in patients with cancer. But along with this, at first glance a positive point, there was another interdisciplinary problem, which is the need for early detection and treatment of developing cardiotoxicity when taking chemotherapy drugs. The study of cardioprotective strategies has recently become increasingly relevant, due to the fact that many patients who have successfully undergone treatment for cancer have a high risk of developing or are at high risk of death from cardiovascular diseases. One of the main drugs for the treatment of a number of oncological diseases is an anthracycline – type antibiotic-doxorubicin. This review briefly examines the risk factors and pathophysiological mechanisms underlying anthracycline cardiotoxicity. The current possibilities of cardioprotection of anthracycline cardiotoxicity are considered in detail, and some promising targets and drugs for improving cardioprotective strategies are discussed.